Priming With Childhood Constructs Influences Distance Perception - Suszek, Hubert; Kofta, Mirosław; Kopera, Maciej (Frontiers in Psychology, 2020)
The aim of our study was to examine whether priming adults with childhood constructs changes distance perception. Two alternative hypotheses could be derived: 1) The fundamental reference approach in visual perception of sizes and distances predicts that priming with childhood constructs should enlarge perceived distance (the world should be larger to a small observer); 2) and, conversely, the action-specific account of perception predicting that priming with childhood constructs should make distances seem shorter (a more physically active child should underestimate distances as more attainable). The results consistently support the second theory. Experiment 1 showed that being either explicitly or implicitly primed with childhood constructs decreased perceptions of distance as compared to that evaluated in the control groups. This effect was noticeable for long distances, and only marginally significant for short distances. Also, this effect was not mediated by mood. Experiment 2 replicated the result of explicit priming with an additional control condition (baseline). The effect remained significant after controlling for the participants’ evaluation of their childhood memories, tendency to relive memories from their childhood, having children, having a driver’s license and the participants’ height.